No Neighbors’ Lands in Postwar Europe
XVIII, 422 p. 14 illus., 8 illus. in color.
Keywords: This book focuses on the social voids that were the result of occupation, genocide, mass killings, and population movements in Europe during and after the Second World War. Historians, sociologists, and anthropologists adopt comparative perspectives on those who now lived in ‘cleansed’ borderlands. Its contributors explore local subjectivities of social change through the concept of ‘No Neighbors’ Lands’: How does it feel to wear the dress of your murdered neighbor? How does one get used to friends, colleagues, and neighbors no longer being part of everyday life? How is moral, social, and legal order reinstated after one part of the community participated in the ethnic cleansing of another? How is order restored psychologically in the wake of neighbors watching others being slaughtered by external enemies? This book sheds light on how destroyed European communities, once multi-ethnic and multi-religious, experienced postwar reconstruction, attempted to come to terms with what had happened, and negotiated remembrance. Anna Wylegała is a sociologist and is Assistant Professor at the Institute of Philosophy and Sociology of the Polish Academy of Sciences in Warsaw. She is the author of Displaced Memories: Remembering and Forgetting in Post-War Poland and Ukraine (2019) and the co-editor (with Małgorzata Głowacka-Grajper) of The Burden of the Past: History and Identity in Contemporary Ukraine (2020). Sabine Rutar is Senior Researcher at the Leibniz Institute for East and Southeast European Studies in Regensburg, Germany, where she works as Editor-in-Chief and Managing Editor of Comparative Southeast European Studies. In her forthcoming monograph At Work under Hitler and Tito: Mining and Maritime Industries in Yugoslavia, 1940s–1960s she compares microhistories of industrial labour during World War II and the early Cold War. Małgorzata Łukianow is a sociologist and is Assistant Professor at the Institute of Philosophy and Sociology of the Polish Academy of Sciences in Warsaw. Her work is situated at the intersection of the sociology of culture, memory studies, and the sociology of knowledge. Chapter 7 and 13 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.